2019
DOI: 10.2169/internalmedicine.2640-19
|View full text |Cite
|
Sign up to set email alerts
|

Primary IgA Vasculitis with Nephritis in a Patient with Rheumatoid Arthritis Diagnosed by Anti-galactose-deficient IgA1 Immunostaining

Abstract: Renal disease is a common complication of rheumatoid arthritis (RA) and can occur secondary to RA or be induced by therapeutic agents. Recently, glomerular deposition of galactose-deficient IgA1 (Gd-IgA1) was identified as a feature of primary IgA vasculitis with nephritis (IgA-VN). We herein report a case of IgA-VN in an RA patient whose disease activity was controlled by treatment with etanercept. To distinguish between primary IgA-VN and secondary IgA-VN caused by RA or etanercept, we performed immunostaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In the present case, we performed a renal biopsy immediately after gross hematuria following a second mRNA-COVID-19 vaccination; the patient was diagnosed with IgAN. Furthermore, there is increasing evidence that IgA deposits in glomeruli in patients with primary IgAN are Gd-IgA1; this procedure involves staining kidney sections using monoclonal antibody against Gd-IgA1 (KM55) (11,12). In this case, Gd-IgA1 colocalized with IgA deposits, indicating that the present patient had gross hematuria due to the transient exacerbation of IgAN following mRNA vaccine BNT 162b2.…”
Section: Discussionmentioning
confidence: 86%
“…In the present case, we performed a renal biopsy immediately after gross hematuria following a second mRNA-COVID-19 vaccination; the patient was diagnosed with IgAN. Furthermore, there is increasing evidence that IgA deposits in glomeruli in patients with primary IgAN are Gd-IgA1; this procedure involves staining kidney sections using monoclonal antibody against Gd-IgA1 (KM55) (11,12). In this case, Gd-IgA1 colocalized with IgA deposits, indicating that the present patient had gross hematuria due to the transient exacerbation of IgAN following mRNA vaccine BNT 162b2.…”
Section: Discussionmentioning
confidence: 86%
“…In seven cases, all in patients treated with rituximab, IGD appeared within the first month of treatment, whereas in four cases (16.0%) IGDs had a long latency onset, and renal disorders developed after 2 years of treatment. Seven of the 25 patients were classified as affected by GNSV (Table 1 ) [ 18 22 ], seven as affected by IARD (Table 2 ) [ 23 28 ] and 11 as affected by GNLS (Table 3 ) [ 29 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients treated with etanercept [ 18 , 19 ], secukinumab [ 20 ] and tofacitinib [ 21 ], and three patients treated with rituximab [ 22 ], developed GNSV, showing crescentic mesangial immunoglobulin A (IgA) deposits in the context of Schönlein–Henoch vasculitis (two cases, 28.6%) [ 18 , 21 ] or necrotizing crescentic glomerulonephritis with clinical and serological pictures of myeloperoxidase anti-neutrophil cytoplasmic antibodies (MPO-ANCA) vasculitis (two cases [28.6%]) [ 19 , 20 ], one of whom also presented mesangial IgA deposits [ 19 ]. Three patients affected by hepatitis C virus-related cryoglobulinemic vasculitis had a renal flare after rituximab treatment and presented deterioration of the known membrane-proliferative glomerulonephritis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Purpura nephritis, also called Henoch-Schönlein purpura nephritis, is a systemic disease with small dead vasculitis as the main pathological change[ 1 - 3 ]. Clinical studies have suggested that the disease is caused by stimuli such as parasitic infections and drug or food allergies[ 4 , 5 ], and epidemiological analysis has shown that the incidence of the disease has increased in recent years[ 6 ].…”
Section: Introductionmentioning
confidence: 99%